Analisis Perkembangan Reksa Dana Syariah dan Sukuk di Indonesia - Muhammad Ash-Shiddiqy (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2025)
The Islamic capital market in Indonesia has experienced significant developments in recent years. The two main instruments in the Islamic capital market are Islamic mutual funds and sukuk. The purpose of compiling this mini-research is to understand how the development of sharia capital market products in Indonesia, in this case, are sharia sharia bonds and mutual funds. The research method used in this mini research is secondary data analysis and literature review. This mini research discusses that Islamic Mutual Funds are investment products based on Islamic principles, while Sukuk are Islamic financial instruments similar to conventional bonds. Increased public awareness and government policies have driven rapid growth in the Islamic Mutual Funds industry. In addition, the Sukuk market has also experienced significant development, strengthening Indonesia's position as one of the largest sukuk markets in the world. Nonetheless, there are still challenges in terms of public understanding and regulations that need to be improved. With better understanding, education, and proper regulation development, Sharia Mutual Funds and Sukuk have the potential to continue to grow and contribute to the Islamic investment industry in Indonesia.